1999
DOI: 10.1159/000054444
|View full text |Cite
|
Sign up to set email alerts
|

Cyclical Variations in the Abundance of Leptin Receptors, but not in Circulating Leptin, Correlate with NPY Expression during the Oestrous Cycle

Abstract: We have demonstrated previously that pharmacological doses of oestradiol decreased leptin receptor expression in the hypothalamus. We therefore analysed leptin receptor expression during the oestrous cycle in the rat, to establish if acute changes in oestradiol affect leptin receptor expression under physiological conditions. Radioactive in situ hybridization histochemistry was used to measure the gene expression under investigation. Total leptin receptor transcript levels were lowest in pro-oestrus in the cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 44 publications
5
50
1
Order By: Relevance
“…These results, together with those obtained in this work, suggest that oestrogens could be exerting a negative feedback on the expression of leptin receptors in the hypothalamic tissue. These data support the results obtained by Bennett et al (1998Bennett et al ( , 1999 who demonstrated that oestrogens modulate the expression of the hypothalamic leptin receptors. On the other hand, it is likely that the expression of leptin receptors in the peripheral tissues is also modulated by steroids, since a positive relationship between steroids and leptin receptors in both the pituitary and ovarian tissue seems to exist.…”
Section: Ctrlsupporting
confidence: 92%
“…These results, together with those obtained in this work, suggest that oestrogens could be exerting a negative feedback on the expression of leptin receptors in the hypothalamic tissue. These data support the results obtained by Bennett et al (1998Bennett et al ( , 1999 who demonstrated that oestrogens modulate the expression of the hypothalamic leptin receptors. On the other hand, it is likely that the expression of leptin receptors in the peripheral tissues is also modulated by steroids, since a positive relationship between steroids and leptin receptors in both the pituitary and ovarian tissue seems to exist.…”
Section: Ctrlsupporting
confidence: 92%
“…This ovarian modulation of feeding involves a phasic, or cycling, inhibition that is mediated by decreased food intake during estrus in intact rats [19]. We and others have previously shown that there are no significant variations in circulating leptin levels during the estrous cycle in rats [17,30]. This is concordant with the results in this study, where no changes were seen between day 2 (proestrus) and day 3 (estrus).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, estradiol levels vary throughout the cycle with peak levels in pro-estrus and lower levels during the other stages [17,22]. A reduction in food intake, preceded…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several neurotransmitters and receptors exhibiting sexual dimorphisms in ARC and its surroundings, such as noradrenalin, galanin, NPY, neurotensin, ␤-endorphin, glutamate, proopiomelanocortin, and leptin receptors have been reported to show estrous cycle-related changes (14,(25)(26)(27)(28)(29). These molecules have been thought to contribute to energy homeostasis and reproductive functions.…”
Section: Discussionmentioning
confidence: 99%